KUALITAS SENSORIS DAN AKTIVITAS ANTIOKSIDAN SELAI UMBI BIT (Beta Vulgaris L.) DENGAN PENAMBAHAN VARIASI KONSENTRASI LABU KUNING (Cucurbita moschata) - Aan Sofyan; Wilia Afida (Universitas Tanjungpura, 2019)
Diversification of food products is an effort in order to realize a food security. Indonesia has a variety of food sources that can be developed into various food products. One of the available food sources is beetroot, which can be used to make jam products. Jam is a processed food product that is usually made by cooking fruit that contains pectin and the addition of sugar and acids. Source of pectin that can be used in the process of making jam is pumpkin. This study aims to determine the antioxidant activity and sensory quality of beetroot jam with the addition of pumpkin. The experimental design uses a completely randomized design with variations in the treatment of pumpkin addition by 0% (LK10), 15% (LK15), 30% (LK30), and 45% (LK45). Static analysis using the Kruskal Wallis test, to see the effect of treatment of the analyzed parameters. The results of antioxidant activity testing using DPPH method on beetroot jam with the addition of pumpkin by 0%, 15%, 30%, and 45% respectively were 53.33%, 43.31%, 40.38%, and 35 99%. The panelists' preference test showed the effect of adding different yellow pumpkins on beetroot jam on the acceptability score of taste and texture, while for other acceptability parameters both color, aroma, and overall did not show any influence. Overall, the most preferred jam product is beetroot jam with 45% pumpkin.